Dynamic conservation of maize landraces by family farmers in Minas Gerais, Brazil - Fernandes, Gabriel (Agrociencia Uruguay, 2022)
Seed replacement promoted by agricultural modernization generated predictions of the disappearance of landraces. Family farmers, however, still keep their seeds contributing to on farm conservation. This study analyzes the structure and dynamics of a local seed system and the reasons that lead farmers to maintain their maize landraces even in the presence of commercial varieties. Twenty farmers in the Zona da Mata of Minas Gerais, Brazil, were interviewed based on indications made by local leaders. The results show that farmers actively maintain diversified channels of access to seeds for planting and new varieties, with an emphasis on family and community relationships. Participation in events expands access to new varieties. Maize landraces have food and agronomic qualities that justify their maintenance. It is concluded that landraces generate autonomy and are at the same time the result of farmers' autonomy in relation to local genetic resources, and their conservation depends on their free access to agrobiodiversity as well as their constant selection to adapt to their productive systems and uses.